Peran Pengawas Minum Obat Terhadap Keberhasilan Pengobatan Tuberculosis dengan Strategi DOTS di Puskesmas Oebobo Kota Kupang - Ni Nyoman Yuliani; Indrawati Maria; Legaletha Tadeus Andre; Novita Saal (Badan Penelitian dan Pengembangan Daerah Kota Kupang, 2019)
Tuberculosis is an infectious disease caused by the bacteria Mycobacterium tuberculosis. Treatment of this disease requires a long time, which is about 6-7 months, this long period of treatment allows the patient to be obedient in taking medication. To prevent this, tuberculosis treatment requires a Drugs Supervisor (PMO). The purpose of this study was to determine the role of the Superintendent of Taking Drugs on the success of tuberculosis treatment with the DOTS strategy for 6 months (July 2017-January 2018) at the Oebobo Health Center. This research is a descriptive study, with a sample of 30 people consisting of 20 men (66.66%) and 10 women (33.34%). The results of this study indicate the percentage of cure rates are 100% and the percentage of active PMO (60%) and inactive (40%). This shows that the awareness of patients to recover is quite high, even though there are 40% inactive PMO, the patient's recovery reaches 100%.